Evaluation of safety of helmets using a featureless Hybrid III headform. (7th November 2006) - Deb, A.; Biswas, U.; Ruan, J.; Gupta, N.K.
This paper proposes a new procedure for designing helmets for head impact protection to road users such as two-wheeler riders and pedestrians. The new procedure suggests that a helmet be mounted on a featureless Hybrid III headform that is used for assessing upper interior head impact safety specified in the vehicle safety standard FMVSS 201 in the USA. To ascertain a helmet's effectiveness as a countermeasure for minimising the risk of severe head injury, an impact velocity of 6 m/s (13.5 mph) was used for the helmet-headform system striking a rigid target. The resultant head impact response is measured by Head Injury Criterion (HIC). The threshold HIC(d) limit of 1000 is applied for adjudging the efficacy of helmets. The proposed procedure is demonstrated with the help of a validated LS-DYNA model of a featureless Hybrid III headform and a helmet. The helmet model consists of an outer General Electric (GE) plastic-based shell to the inner surface of which is bonded a protective energy-absorbing foam padding of a given thickness. Based on simulation results of impact on a rigid surface, it appears that foam padding of suitable strength and a minimum thickness of 35–40 mm along with a shell thickness of 3–4 mm is necessary for obtaining an acceptable value of HIC(d), and therefore, an acceptable helmet safety design.